Colorimetric detection of acetylcholine with plasmonic nanomaterials signaling - Oh, Ju-Hwan; Kim, Byoung Chan; Lee, Jae-Seung (SPRINGER HEIDELBERG, 2014)
We have developed a highly sensitive and selective colorimetric method for detection of acetylcholine (ACh), using a tandem enzymatic reaction for biological target recognition and silver nanoplates (AgNPLs) for optical signal generation. The ACh molecules are enzymatically hydrolyzed and oxidized into betaine and hydrogen peroxide, the latter of which chemically oxidizes the AgNPLs to generate the "turn-on" signal. To optimize detection sensitivity, the chemical and biological properties of the detection mixtures containing the enzymes, ACh, and AgNPLs were thoroughly investigated with respect to component concentrations and reaction temperatures; a maximum sensitivity of 500 nM for colorimetric detection of ACh was achieved. We further directly compared the signaling profiles of (1) novel nanostructured and (2) conventional molecular chromogens, improving our understanding of the factors that should be considered when designing a detection system.
Keywords: GOLD NANOPARTICLES; SILVER NANOPARTICLES; HYDROGEN-PEROXIDE; OPTICAL-DETECTION; AU NANOPARTICLES; O-DIANISIDINE; DNA DETECTION; NANORODS; GLUCOSE; CHOLINE